Wellbore integrity factors for CO2 storage in oil and gas producing areas in the Midwest United States. Issue 5 (4th May 2016) - Sminchak, J.R.; Moody, Mark; Gupta, Neeraj; Larsen, Glenn
Abstract: The condition of legacy oil and gas wells is an important issue for geologic CO2 storage projects. Many regions with large CO2 point sources coincide with historical oil and gas fields. This is especially apparent in the Midwestern United States, where over one million oil and gas wells are present dating back to the late 1800s. To investigate wellbore integrity factors in this region, the condition of oil and gas wells in Michigan and Ohio was summarized based on well status, depth, construction, age, and plugging specifications. To better understand the impact of well integrity on a local scale, six test study areas were also analyzed. These hypothetical test study areas were based on subsurface area necessary for an industrial scale CO2 storage application. Detailed records were used to categorize well conditions, and corrective actions necessary to repair the wells were then assigned. The results of the test study area analysis provide a real representation of the level of effort necessary to prepare sites for CO2 storage. Actions may involve relatively low‐effort tasks to examine wellheads or more extensive well re‐entry and plugging. The analysis indicated that many areas may have hundreds of wells, but no wells penetrating the deeper CO2 storage zones. At sites where many wells require corrective action, it may be challenging to efficiently plug and abandon wells. Options such as testing wellhead pressures, surface monitoring of CO2 leakage, and less extensive plugging requirements may help offset costs associated with remediating a large number of wells. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd.